PENGUKURAN TINGKAT KEPUASAN PENGUNJUNG DI OBJEK WISATA PUNCAK TEMBOAN DESA RURUKAN SATU KOTA TOMOHON - Deddy Kaligis; Jen Tatuh; Lorraine W. Th. Sondak; Ellen G. Tangkere (Universitas Sam Ratulangi, 2014)
ABSTRACTIn Tomohon there are various places that could be tourist destinations and Puncak Temboan is one of them. In order to increase tourist visits, visitor satisfaction must be considered. A visitor satisfaction can be realized only through the improvement of service quality. The objective of research is to determine the level of visitor satisfaction in Puncak Temboan Tourism Object.This study was conducted from April to June 2014. Population in this study were visitors of Puncak Temboan Tourism Object. Samples taken were 50 repondents using accidental sampling method.The results of this study showed that the level of visitor satisfaction with quality of services as a whole was in the satisfied category. However, there are still indicators that had a high interest level and low performance and should receive more attention from the manager of the Puncak Temboan Tourism Object. The manager of Puncak Temboan Tourism Object need to maintain service quality indicators that have been assessed well by visitors and also the need to improve the indicators still considered less well by the visitors